Aeroelastic control of bridge using active control surfaces: Analytical and experiment study. (October 2020) - Phan, Duc-Huynh
Abstract: An active control using a control surface system with winglets is described herein. Winglets help a long suspension bridge reach a stable state of flutter and buffeting. This system ensures the aerodynamic stability of a lightweight and economic stiffening girder without additional stiffening. Using a two-dimensional model, numerical and experimental studies were carried out to find a feedback control using winglets. In conclusion, a suitable control of the winglet motion can increase the flutter speed of a suspension bridge as the buffeting response moves in a contrasting manner.